Materiovigilance in surgical care: A cross-sectional KAP study among surgeons. - Deolekar, Pradnya; Dongerkery, Kavitha; Deolekar, Sandesh; Navya, Movva; Dahibhate, Atharva; D.T, Prateek; Sinha, Akash; Rane, Veena; Sawant, Yuvraj; Vadhavekar, Nidhi Hrishikesh (Student’s Journal of Health Research Africa, 2025)
Background: Surgical devices and instruments play a vital role in patient safety and clinical outcomes. Materiovigilance, the systematic monitoring of adverse events and risks associated with medical devices, is essential in ensuring safer surgical practice. Objective: To assess the knowledge, attitudes, and practices (KAP) of surgeons regarding materiovigilance in surgical care. Methods: A cross-sectional, questionnaire-based study was conducted among practicing surgeons from various specialties in Navi Mumbai. The survey explored knowledge of materiovigilance, reporting practices, barriers to reporting, and attitudes towards medical device safety. Results: A total of 149 surgeons participated. About 67.8% correctly identified India’s Materiovigilance Programme (MvPI), and 75.2% were aware that all healthcare professionals can report device-related adverse events. While 69.1% acknowledged that surgical devices may cause adverse events, 85.2% felt reporting was a surgeon’s responsibility, and 80.5% supported making it mandatory. Nearly half (48.3%) had encountered a device-related adverse event, but only 25.5% reported it. Notably, 80.5% had never received formal training on adverse event reporting. Conclusion: Awareness regarding materiovigilance among surgeons was suboptimal. Strengthening training, creating user-friendly reporting platforms, and integrating materiovigilance into surgical practice are crucial for improving patient safety. Recommendation: Regular training programs on materiovigilance, simplified and accessible reporting systems, and mandatory integration of device safety reporting into routine surgical practice are recommended to enhance reporting compliance and patient safety.